Development of A Web-Based Employee Performance Monitoring and Reporting System to Enhance Productivity and Performance Evaluation - Devina, Annisa; Nasution, Darmeli (Cattleya Darmaya Fortuna, 2025)
The Attorney General's Office, as a law enforcement institution, requires optimal employee performance to achieve effectiveness in law enforcement. However, the current employee performance monitoring and reporting processes at the Binjai District Attorney's Office are still manual, leading to inefficiencies, lack of transparency, and difficulties in objective evaluation. This research aims to develop a Web-Based Employee Performance Monitoring and Reporting System as a solution to address these issues. The system is designed to improve the accuracy, transparency, and integration of performance data, thereby enabling more objective and measurable evaluations. With this system, leaders can provide accurate feedback, identify performance problems earlier, and ultimately enhance employee productivity and the overall performance of the Attorney General's Office. The research has successfully developed a web-based system with an interface that allows centralized management of user data, employee information, tasks, and performance evaluations. The implementation of this system is expected to significantly positively impact operational efficiency and support the achievement of organizational goals in more effective and efficient law enforcement.